2007
DOI: 10.1111/j.1525-142x.2007.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental origin of the adult nervous system in a holothurian: an attempt to unravel the enigma of neurogenesis in echinoderms

Abstract: In adult echinoderms, the nervous system includes the ectoneural and hyponeural subsystems. The former has been believed to develop from the ectoderm, whereas the latter is considered to be mesodermal in origin. However, this view has not been substantially supported by embryological examinations. Our study deals with the developmental origin of the nervous system in the direct-developing sea cucumber Eupentacta fraudatrix. The rudiment of the adult nervous system develops from ectodermally derived cells, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Hence, most, if not all, of the larval nervous system is discarded at metamorphosis, and the adult nervous system is composed of a completely different set of cells in O. japonicus. The same has been previously suggested in asteroids (Byrne and Cisternas 2002;Nezlin et al 1991), ophiuroids (Dupont et al 2009;Hirokawa et al 2008), and holothuroids (Mashanov et al 2007;), but the observations on the feather star O. japonicus here are the first to show that the larval nervous system does not participate in the formation of the aboral nerve center of crinoids. Since it is probable that the aboral nervous system was morphologically and functionally the dominant nervous system in early echinoderms (Paul and Smith 1984), we propose here that the main adult nervous system was formed relatively early in ontogeny and independent from the larval nervous system in the common ancestor of echinoderms.…”
Section: Comparisons With Other Echinodermssupporting
confidence: 74%
See 1 more Smart Citation
“…Hence, most, if not all, of the larval nervous system is discarded at metamorphosis, and the adult nervous system is composed of a completely different set of cells in O. japonicus. The same has been previously suggested in asteroids (Byrne and Cisternas 2002;Nezlin et al 1991), ophiuroids (Dupont et al 2009;Hirokawa et al 2008), and holothuroids (Mashanov et al 2007;), but the observations on the feather star O. japonicus here are the first to show that the larval nervous system does not participate in the formation of the aboral nerve center of crinoids. Since it is probable that the aboral nervous system was morphologically and functionally the dominant nervous system in early echinoderms (Paul and Smith 1984), we propose here that the main adult nervous system was formed relatively early in ontogeny and independent from the larval nervous system in the common ancestor of echinoderms.…”
Section: Comparisons With Other Echinodermssupporting
confidence: 74%
“…Reports from asteroids, ophiuroids, and holothurians showed that none of the larval nervous system is incorporated into the adult nervous system (Byrne and Cisternas 2002;Dupont et al 2009;Hirokawa et al 2008;Mashanov et al 2007;Nakano et al 2006;Nezlin et al 1991). But there has been only one complete report of nervous system development, from embryos to juveniles, in a species with a primitive type of development for echinoderms: a dipleurula-type larva followed by a doliolaria larva .…”
Section: Introductionmentioning
confidence: 94%
“…The nerve ring and the outer parts of the nerve cord belong to the ectonerual compartment, whereas the inner layer of the nerve cords is the hyponeural system. These two systems were thought to be separate; however, fine-structural studies and histochemistry of neurotransmitters in sea cucumbers have indicated that both systems are derived from ectoderm and are interconnected (Mashanov et al, 2007;Hoekstra et al, 2012). Moreover, Echinoderms also have numerous ectodermal sensory cells.…”
Section: Introductionmentioning
confidence: 99%
“…) and automated procedures (prealignment, generation of final geometric models, etc.) mostly surface (rendering) models of specimens or specimen components are generated (see e.g., Haas et al, 2006;Mashanov et al, 2007;Neusser et al, 2006;Ruthensteiner, 2006;Taguchi and Kohsuke, 2003). These are particularly appropriate as interactive PDF models, since with the aid of the Adobe software 3D Toolkit (included in Acrobat 3D software package) these models can easily be converted to a format suitable for PDF files.…”
Section: Introductionmentioning
confidence: 99%